2013
DOI: 10.1002/mnfr.201300112
|View full text |Cite
|
Sign up to set email alerts
|

Genistein alleviates the development of nonalcoholic steatohepatitis in ApoE―/― mice fed a high‐fat diet

Abstract: GEN alleviated NASH as well as hypercholesterolemia and obesity in ApoE(-/-) mice fed an HFD. Restoration of altered cholesterol metabolism and oxidative stress may be involved in the protective effect of GEN against NASH development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 45 publications
6
42
3
Order By: Relevance
“…In addition, when administered within the diet, genistein can lower protein levels of CD36 and improve blood lipid levels and the degree of nonalcoholic fatty liver in ApoE-/-rats [27]. As expected, by using oil red O staining and cholesterol ester determinations, we demonstrated ( Figure 1) that genistein (10 or 50µmol/L) and herbimycin A suppressed intracellular lipid accumulation in SMCs, while daidzein had no effect.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, when administered within the diet, genistein can lower protein levels of CD36 and improve blood lipid levels and the degree of nonalcoholic fatty liver in ApoE-/-rats [27]. As expected, by using oil red O staining and cholesterol ester determinations, we demonstrated ( Figure 1) that genistein (10 or 50µmol/L) and herbimycin A suppressed intracellular lipid accumulation in SMCs, while daidzein had no effect.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 53%
“…In addition, genistein can lower protein levels of CD36 and improve blood lipid levels and the degree of non-alcoholic fatty liver in ApoE-/-rats [27]. However, limited research of genistein has been directed at examining its role in inhibiting the formation of SMC-derived foam cells.…”
Section: Studies From Epidemiological Investigations Have Indicated Tmentioning
confidence: 98%
“…Genistein, one of the major isoflavones in soybeans, has antioxidant and phytoestrogenic activities that may contribute to its potential anti-inflammatory, anticarcinogenic, and hypocholesterolemic effects [18,19]. We have previously reported that genistein alleviated NASH as well as hypercholesterolemia and obesity in ApoE −/− mice fed a high-fat diet (HFD), suggesting that restoration of altered cholesterol metabolism and inhibition of oxidative stress and inflammation may be involved in the protective effect of genistein against NASH development [18].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that genistein alleviated NASH as well as hypercholesterolemia and obesity in ApoE −/− mice fed a high-fat diet (HFD), suggesting that restoration of altered cholesterol metabolism and inhibition of oxidative stress and inflammation may be involved in the protective effect of genistein against NASH development [18]. We also observed the inhibitory effect of isoflavones against endoplasmic reticulum (ER) stress-induced cell death and tau hyperphosphorylation in neuroblastoma cells [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Unstressed ( n = 14) and SCUMS ( n = 14) hamsters, of which unstressed ( n = 7) and stressed ( n = 7) animals were fed daily with genistein-enriched chow (500 mg/kg diet) [18] for 14 days with respect to their corresponding controls ( n = 14) fed with normal chow, were evaluated. The SCUMS group was exposed to the following stressful conditions for 14 days: light/dark cycle inverted, deprivation of water, inclination of cage, empty bottle, and wet litter.…”
Section: Methodsmentioning
confidence: 99%